The Effect of Price Discount and Store Atmosphere on Positive Emotion - M. Risal; Andi Nadirah; Ramli Ramli (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
The focus of this research is to see how the influence of Price Discount and Atmosphare store on Positive Emotion on consumers Alfamidi Palopo City. This research is categorized as quantitative research with data collected through questionnaires. Where the sample in this study were 87 people. The collected questionnaires were processed with the help of the SPSS 25 application. Based on the SPSS processing, it was found that the Price Discount and Atmosphare store had a significant effect on Positive Emotion on Alfamidi consumers in Palopo City with a positive direction. The direction of positive influence means that the more often the Price Discount is given by Alfamidi, the more positive Emotion will be on Alfamidi's consumers in Palopo City. The better the Atmosphare store perceived by Alfamidi consumers, the more positive Emotion will be for Alfamidi consumers in Palopo City.